THE ROLE OF TPA DAARUL IQRO TEACHERS IN FOSTERING CHILDREN'S MORALS IN BABAKAN LEBAK BOGOR CITY - Khaidir Fadil; Budiyanto; Syarifah Gustiawati (Al-Mubin, 2023)
Research at TPA Daarul Iqro is a highlight that makes how the morals of the children at TPA Daarul Iqro are considered. The purpose of this study was to determine the role of the Daarul Iqro Al-Qur'an Education Park (TPA) Teacher in fostering children's morals. To find out the influencing factors in fostering children's morals at TPA Daarul Iqro. This research uses qualitative methods with a field study approach. Techniques in data collection used in this study are; observation, interviews and documentation. The type of interview used is an unstructured interview. The results of this study found that the role of the TPA teacher is not only teaching but also being a mentor, moral coach, as a guide / role model, TPA teachers must also be able to act as facilitators and motivators. supporting factors for moral development are parents, motivation and the surrounding environment, as well as inhibiting factors Peer groups and mass media. So, it can be concluded that the role of the TPA teacher in fostering morals is that the teacher not only play a role as a teacher, but also the teacher must be able to be a mentor, moral coach and facilitator